X-irradiation of developing hippocampal neurons causes changes in neuron population phenotypes, dendritic morphology and synaptic protein expression in surviving neurons at maturity. (November 2020) - Puspitasari, Anggraeini; Yamazaki, Hiroyuki; Kawamura, Hidemasa; Nakano, Takashi; Takahashi, Akihisa; Shirao, Tomoaki; Held, Kathryn D.
Highlights: Exposure of immature neurons to 0.5−1 Gy of X-rays causes a gradual reduction of number of neurons. The X-irradiation changes the percentage of inhibitory neurons among the remaining neurons. Delayed reduction of the postsynaptic proteins drebrin and PSD-95 after irradiation is found. Abstract: The effects of X-irradiation on developing neurons and their functions are unclear. We used primary cultures of mouse hippocampal neurons to investigate the effects of X-irradiation on cell death in developing neurons by analyzing caspase-3, MAP2 and DAPI-labeled cells, and the phenotypes and function of surviving neurons, by examining GAD67-positive cells as a GABAergic marker, and the synaptic markers synapsin 1, drebrin and PSD-95 through its maturation. One-day in vitro (DIV 1) cells were exposed to 0.5 Gy or 1 Gy of X-rays. A significant increase in the percentage of activated caspase-3, a decrease in the number of MAP2/DAPI-positive cells and change in the percentage of GAD67 positive neurons, compared with sham controls, were found 6 days after 1 Gy and 13 days after 0.5 Gy of X-rays. The expression of PSD-95 and drebrin, as well as drebrin clusters, in the remaining neurons was decreased at DIV 21, in both 0.5 Gy and on 1 Gy-irradiation there was a reduced number of dendritic intersection as well. Together, our findings show that 0.5 Gy and 1 Gy of X-irradiation at DIV 1 not only causes neuronal cell death but elicits an increase in the percentage of inhibitory neurons, changes in the dendrites and decrease in expression of important synaptic proteins in the surviving neurons at maturity 3 weeks after exposure.